Measurement of Fiscal Impact : Methodological Issues: Occa Paper 59. (Occasional Papers; Occasional Paper ;, 1988)
This paper describes methodological issues pertaining to measurement of fiscal impact. The fiscal deficit is, under any circumstances, a crude tool for assessing the impact of fiscal policy on the economy. This paper also analyzes various ways in which the conventional definition of the fiscal deficit is affected by high rates of inflation. It has shown that, as the rate of inflation rises, the picture emerging from the conventional measure may, under certain circumstances, become somewhat blurred since the conventional measure may magnify the size of the fiscal adjustment that a country need. In fact, the size of the debt service that compensates bondholders for the reduction in the real value of their assets arising from inflation should be made explicit so as to indicate that part of the deficit whose impact depends mainly on portfolio decisions regarding the public's demand for government bonds, and on the potential effects of these bonds on the monetary and liquidity conditions of the economy.